Lactic Acid Bacteria Mixture Isolated From Wild Pig Alleviated the Gut Inflammation of Mice Challenged by Escherichia coli - Yifan Zhong; Dongyan Fu; Zhaoxi Deng; Wenjie Tang; Jiangdi Mao; Tao Zhu; Yu Zhang; Jianxin Liu; Haifeng Wang (Frontiers in Immunology, 2022)
Wild pigs usually showed high tolerance and resistance to several diseases in the wild environment, suggesting that the gut bacteria of wild pigs could be a good source for discovering potential probiotic strains. In our study, wild pig feces were sequenced and showed a higher relative abundance of the genus Lactobacillus (43.61% vs. 2.01%) than that in the domestic pig. A total of 11 lactic acid bacteria (LAB) strains including two L. rhamnosus, six L. mucosae, one L. fermentum, one L. delbrueckii, and one Enterococcus faecalis species were isolated. To investigate the synergistic effects of mixed probiotics strains, the mixture of 11 LAB strains from an intestinal ecology system was orally administrated in mice for 3 weeks, then the mice were challenged with Escherichia coli ATCC 25922 (2 × 109 CFU) and euthanized after challenge. Mice administrated with LAB strains showed higher (p < 0.05) LAB counts in feces and ileum. Moreover, alterations of specific bacterial genera occurred, including the higher (p < 0.05) relative abundance of Butyricicoccus and Clostridium IV and the lower (p < 0.05) abundance of Enterorhabdus in mice fed with mixed LAB strains. Mice challenged with Escherichia coli showed vacuolization of the liver, lower GSH in serum, and lower villus to the crypt proportion and Claudin-3 level in the gut. In contrast, administration of mixed LAB strains attenuated inflammation of the liver and gut, especially the lowered IL-6 and IL-1β levels (p < 0.05) in the gut. Our study highlighted the importance of gut bacterial diversity and the immunomodulation effects of LAB strains mixture from wild pig in gut health.